The common sense behind basic economics : a guide for budding economists, students, and voters - Vélez-Hagan, Justin (Lexington Books, 2015)
Economics really is just common sense, but few understand the basics. This book explains the basics of economics in simple, easy-to-understand language. Topics include most of the themes presented in an Economics 101 course, as well as a number of end-of-chapter discussions on the policies relevant to economics today.